Microbiota associated with urban forests - Xin Wan; Runyang Zhou; Yingdan Yuan; Wei Xing; Sian Liu (PeerJ, 2024)
Urban forests are essential for maintaining urban ecological stability. As decomposers, soil microorganisms play an indispensable role in the stability of urban forest ecosystems, promoting the material cycle of the ecosystems. This study used high-throughput sequencing technology to explore the bacteria in six forest stands, including Phyllostachys edulis (ZL), Metasequoia glyptostroboides (SSL), Cornus officinalis (SZY), mixed broad-leaved shrub forest (ZKG), mixed pine and cypress forest (SBL), and mixed broad-leaved tree forest (ZKQ). Meanwhile, the differences in fungal communities were investigated. The results show that ZL has the highest alpha diversity of bacterial communities, while its fungal community is the lowest; Proteobacteria is the most abundant bacterial phylum in the six forest stands; ZKQ has the highest fungal diversity. In addition, soil microbial communities are affected by environmental factors. Soil pH, organic matter (SOM), and available phosphorus (AP) significantly influence the compositions of urban forest soil microbial communities. This study revealed the differences in bulk soil (BS) microbial community structures among six forest stands and the relationship between environmental factors and soil microbial communities, which has important guiding significance for creating healthy and stable urban forests with profound ecological benefits.